Risk of Osteoporosis in Patients with Crohn’s Disease Not Respond to Infliximab Therapy Undergoing Surgical Intervention - Fatima A.Mohammad1, Fatin Fadhel ALkazazz2, Sura A.Abdusattar3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Osteoporosis is one of the most common complications of Crohn’s disease (CD). Proper history with blood samples were collected from (30) healthy control group, (30) Crohn’s disease patients have been respond to biological therapy ( infliximabIFX) (response group) and (30) CD patients with (non-response group) to biological therapy undergoing surgical intervention for the estimation of some biochemical parameters. This study demonstrate a significant decrease in FGF-23 (fibroblast growth factor 23) and vitamin D Levels between (non- response group) and control group (p< 0.01). Similary , parathyroid hormone (PTH) Levels were increased significantly ( p< 0.01) in (non- response) group. Moreover the calcium (Ca) and phosphours (P) decreased significantly (p< 0.01) in same group. While in CD patients that have been treated with infliximab only vitamin D and FGF 23 decreased significantly (p< 0.01)compared with control group. Levels of Serum FGF23 are considerably lower in CD patients, It is independent pattern was not affected by type of treatment (medical or surgical) . Hypovitaminosis common finding in CD patient’s .Although CD is not disease of vit D deficiency but it clearly is a disease whose pathogenesis seems closely related to vit D Level.